Economic viability of foreign investment in public transport of Pakistan – orange line metro train in focus. Issue 3 (3rd July 2021) - Ali, Yousaf; Rahman, Abdul; Lala, Shamsher; Sabir, Muhammad
Abstract: Pakistan, like other developing countries, is also facing environmental and economic challenges in its transportation sector (especially in public transport). Pakistan is going to get finances for the infrastructure-related projects under the China-Pakistan Economic Corridor (CPEC) initiative. One of the CPEC projects is the Orange Line Metro Train (OLMT). The study employs traditional techniques such as linear trend regression, benefit-cost ratio (BCR) and geometric progression to analyse the economic viability of the project. The results show that with given interest rate and stability in exchange rate the project is economically viable, with a benefit/cost ratio (BCR) of 2.11 and Internal Rate of Return (IRR) equal to 3.07 per cent. Furthermore, the sensitivity analysis is done for possible changes in economic conditions as well as for different interest rates for loan repayments. The study is useful for policymakers interested in the benefit–cost analysis of public transportation projects.